Assessment and Management of Environmental Risks of Steel Industries by EFMEA Method (Case Study: Ardakan Steel and Melting factory) - Fatemeh Nikpishe Kohjhari; Maryam Morovati; Majid Sadeghinia; Leila Amanat Yazdi (Muhandisī-i Bihdāsht-i Muḥīṭ, 2020)
Background: Industries like steel, along with wealth generation and economic development, create many environmental problems, such as air, water, and soil pollution and waste generation. Since environmental protection is considered one of the pillars of sustainable development, solutions should be adopted that minimize environmental hazards, and promote the existing industry towards sustainable development. . The purpose of this research is to evaluate and manage the environmental risk of Ardakan Steel and Melting Company using the EFMEA method. Method: Firstly, with the field visit of Ardakan Steel and Melting Company, were identified all hazards and environmental aspects and calculated using EFMEA method. Then, the data were analyzed using SPSS software. Regarding corrective actions, a secondary evaluation was performed. Finally, the mean of initial RPN and secondary RPN were analyzed and compared by t-test. Results: In this study, 316 environmental risk factors were identified, of which 39 were at low risk, 139 were at medium level and 138 were high risk. Also, the comparison of the means from the two evaluations showed that the average of initial data decreased from 1466.45 to 1248.16 in the secondary data. Conclusion: The results of this study showed that by choosing the right method and planning and providing preventive and corrective strategies, the environmental hazards of the industries could be significantly reduced.